2018
DOI: 10.1042/bsr20171162
|View full text |Cite
|
Sign up to set email alerts
|

Sterol 27-hydroxylase gene dosage and the antiatherosclerotic effect of Rifampicin in mice

Abstract: Sterol 27-hydroxylase (CYP27A1) catalyzes the hydroxylation of cholesterol to 27-hydroxycholesterol (27-OHC) and regulates cholesterol homeostasis. In Cyp27a1/ Apolipoprotein E (ApoE) double knockout (KO) mice fed with Western diet (WD), the atherosclerotic phenotype found in ApoE KO mice was reversed. As protective mechanism, up-regulation of Cyp3a11 and Cyp7a1 was proposed. Cyp27a1 heterozygote/ApoE KO (het) mice, with reduced Cyp27a1 expression and normal levels of Cyp7a1 and Cyp3a11, developed more severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Cholesterol metabolism has been identified as a modulator of AD that is involved in maintaining synaptic plasticity, neural development, and brain function [ 5 ]. Evidence suggests that 27-OHC plays an essential role in AD [ 11 , 12 , 29 , 30 ]. Moreover, our previous studies have shown that 27-OHC could inhibit cholesterol synthesis in C6 glioma cells [ 18 ] and facilitate the transport of cholesterol from astrocytes to neurons [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol metabolism has been identified as a modulator of AD that is involved in maintaining synaptic plasticity, neural development, and brain function [ 5 ]. Evidence suggests that 27-OHC plays an essential role in AD [ 11 , 12 , 29 , 30 ]. Moreover, our previous studies have shown that 27-OHC could inhibit cholesterol synthesis in C6 glioma cells [ 18 ] and facilitate the transport of cholesterol from astrocytes to neurons [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sterol 27-hydroxylase (CYP27A1) can catalyze the hydroxylation of cholesterol to form 27-OHC mainly in the liver, which is initially released into the blood. 27-OHC is an abundant oxysterol in the blood with an ability to cross the BBB and it plays an essential role in AD pathogenesis [ 10 , 11 , 12 ]. An increasing amount of evidence has demonstrated that the plasma level of 27-OHC in patients with mild cognitive impairment and AD is higher than average [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although not in all cases, most adult CTX patients have normal liver function despite their high cholesterol and 5α-cholestanol [50,51]. Similarly, in an atherogenic mouse model with Cyp27a1 deficiency, Zurkinden et al [92,93] reported that Cyp27a1/ApoE double-knockout mice were resistant to WD-induced liver inflammation, as demonstrated by their lowered hepatic inflammatory and oxidative stress gene expressions (i.e., Tnfα and Il1b). Another study in a goose model reported that hepatic Cyp27a1 mRNA expression can be significantly inhibited in goose fatty livers [94].…”
Section: Cholesterol Metabolites In Mitochondria Impairmentmentioning
confidence: 99%
“…Based on the observations from CTX patients [50,51], Cyp27a1 −/− mice [92,93], and goose fatty liver models [94], it is also reasonable to consider Cyp27a1 inhibition for reducing NASH inflammatory responses. Although no such studies have been reported for NASH intervention, Cyp27a1 inhibition is now being explored for the treatment of breast cancer [128,129] and toxic retinol accumulation in the eye [130].…”
Section: Targeting Mitochondrial Cholesterol Metabolites For Nash Int...mentioning
confidence: 99%